Earnings Management and Firm Performance Around Listing Events: The Moderating Role of Gender - Chi Duong Thi (SAGE Open)
The main purpose of this study is to examine how female representation on the Board of Directors (BOD) and the role of female chief accountants moderate earnings management (EM) concerning firm performance around listing events in Vietnam. Additionally, we aim to investigate whether a substitute (stand-alone) or complementary relationship exists between AEM and REM in both upward and downward forms. While accruals earnings management (AEM) is computed based on accruals proxies, the three measures are aggregated into comprehensive metrics for Real Earnings Management (REM). To achieve these objectives, three hypotheses have been developed after a thorough review of the literature. Panel data has been collected from 222 firms that newly listed over a 4-year span around the listing events. This study demonstrates that the presence of women on BOD significantly and positively moderates the association between positive real-accruals earnings management and firm performance, but this effect is not observed in firms with negative REM or AEM. Our research additionally reveals that there is no moderating role of female chief accountant in these relationships. However, the presence of a female chief accountant positively impacts firm performance only in the positive AEM model. Additionally, we provide evidence that firms may employ individual EM strategies rather than complementary ones, with each type having a positive impact on firm performance.